Three new species of Micropsalliota (Agaricaceae, Agaricales) from China - Li, Jia-Xin; He, Mao-Qiang; Zhao, Rui-Lin (Phytotaxa, 2021)
Species diversity of Micropsalliota in China remains poorly known, especially in southwestern China, a hotspot of biodiversity. Based on morphological characteristics and molecular phylogenetic analyses using ITS and nrLSU sequences, three new species named Micropsalliota delicatula, M. dentatomarginata and M. digitatocystis are introduced from China. Phylogenetc analyses results indicated the unique phylogenetic positions of three new species in Micropsalliota. Full descriptions, photo plates, illustrations and a phylogenetic tree to show the placement of three new species are presented.